Possible roles of robo1+ ensheathing cells in guiding dorsal‐zone olfactory sensory neurons in mouse. Issue 11 (11th September 2013) - Aoki, Mari; Takeuchi, Haruki; Nakashima, Ai; Nishizumi, Hirofumi; Sakano, Hitoshi
ABSTRACT In the mouse olfactory system, the anatomical locations of olfactory sensory neurons (OSNs) correlate with their axonal projection sites along the dorsoventral axis of the olfactory bulb (OB). We have previously reported that Neuropilin‐2 expressed by ventral‐zone OSNs contributes to the segregation of dorsal and ventral OSN axons, and that Slit is acting as a negative land mark to restrict the projection of Robo2+, early‐arriving OSN axons to the embryonic OB. Here, we report that another guidance receptor, Robo1, also plays an important role in guiding OSN axons. Knockout mice for Robo1 demonstrated defects in targeting of OSN axons to the OB. Although Robo1 is colocalized with dorsal‐zone OSN axons, it is not produced by OSNs, but instead by olfactory ensheathing cells. These findings indicate a novel strategy of axon guidance in the mouse olfactory system during development. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73:828–840, 2013